The impact of the euro on trade: Two decades into monetary union - Vanessa Gunnella; Laura Lebastard; Paloma López-García; Roberta Serafini; Alessandro Zona Mattioli (European Central Bank (ECB), 2021)
The consensus back in 2008 - ten years after the introduction of the euro - was that the adoption of a common currency had made a limited impact of around 2% in total on the trade flows of the first wave of euro area countries (Baldwin et al., 2008). Since then, six more countries have joined the euro area, and firms have internationalised their production processes. These two phenomena are interrelated and may have changed the way the common currency affects the euro area economy. Therefore, with the common currency now into its third decade - and with more countries queuing to adopt it - this paper revisits the trade effects of the euro, focusing on the newer euro adopters (i.e. those countries that have adopted the euro since 2007) and their interaction with the first wave of euro area members via supply chains. The contribution of the paper is twofold. First, it revisits the estimated aggregate impact of the euro on euro area trade, as well as on trade within and between the two waves of adopters. Data on bilateral flows between 1990 and 2015 for an extended sample of countries to estimate a gravity equation indicate a significant trade impact, ranging between 4.3% and 6.3% in total on average, with the magnitude being the highest for exports from the second wave of adopters to the first wave of adopters. If a synthetic control approach (Abadie and Gardeazabal, 2003; Abadie et al., 2010) is used instead, the estimated gains associated with euro adoption are greater. In particular, exports of both intermediate and final products from countries belonging to the first wave of euro adopters to those belonging to the second wave are estimated to have increased by about 30% using this approach. The second contribution made by this paper relates to the channels through which trade might be affected by a currency union. This question is explored by looking separately at trade in intermediate goods and final products. While we find that trade gains were mainly driven by trade in intermediate goods among countries that adopted the currency earlier (5.3%), our results also show that the euro had a positive effect on the exports of final products from the second wave of adopters to other euro area countries. This effect is as high as 10.6% with the gravity model and 32% with the synthetic control approach. One of the reasons for the difference in the range of estimates between the two approaches might be that the gravity model can control for unobserved characteristics via fixed effects, while the synthetic control approach may fail to do so. These results suggest that the euro facilitated the establishment and expansion of international production chains in Europe. In turn, this is likely to have increased business cycle synchronisation in the euro area and to have supported market access for later adopters.
Keywords: F14; F15; 330; euro; trade flows; global value chains; gravity equation; synthetic controlapproach